2022
DOI: 10.1242/dev.190421
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial identity is established during early somitogenesis by Bmp signalling acting upstream ofnpas4landetv2

Abstract: The endocardium plays important roles in the development and function of the vertebrate heart; however, few molecular markers of this tissue have been identified and little is known about what regulates its differentiation. Here, we describe the Gt(SAGFF27C); Tg(4xUAS:egfp) line as a marker of endocardial development in zebrafish. Transcriptomic comparison between endocardium and pan-endothelium confirms molecular distinction between these populations and time-course analysis suggests differentiation as early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Endocardial cells are known to share a large transcriptional similarity with other vascular endothelial cells 33 , 60 63 , but they also have their unique identity known by expression of marker genes such as nfatc1 and gata5 64 , 65 . Recent studies have described endocardial transcriptome at 15 and 20-somite stages in zebrafish embryos 48 , 66 . However, endocardial transcriptome at 24 hpf stage has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocardial cells are known to share a large transcriptional similarity with other vascular endothelial cells 33 , 60 63 , but they also have their unique identity known by expression of marker genes such as nfatc1 and gata5 64 , 65 . Recent studies have described endocardial transcriptome at 15 and 20-somite stages in zebrafish embryos 48 , 66 . However, endocardial transcriptome at 24 hpf stage has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant overlap of marker genes, such as fn1a , gata5 , id2b, wnt11r , bmp16 and bambib between the two endocardial clusters (Table S7 ). A recent study reported the zebrafish endocardial transcriptome at the 15-somite stage 66 . There was an extensive overlap between our endocardial dataset and the one reported by Capon et al (Table S7 ), further validating endocardial identity of the nfatc1 + gata5 + cell cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that endocardial-specific identity may be established as early as the 8-somite stage. 54 Therefore it is likely that endocardial-derived hematopoiesis initiates prior to the 24-hpf stage, and double-positive kdrl:GFP - and spi1b -positive cells observed at the 16-somite stage may mark early endocardial-derived myeloid cells.…”
Section: Discussionmentioning
confidence: 99%